Access Controlled High Speed Corridor and Urban Development of Kerala. (2016) - Sujith, K.M.
Abstract: The urban development scenario of Kerala state has always been struggling due to the heavy dependence on the existing overloaded transport network. It has been more than a decade since the ambitious project to develop a 526 km long access controlled high speed corridor linking the northern and southern most cities of Kerala was shelved. This project could not be materialized due to the protest from various corners voicing their concerns regarding how it was going to impact Kerala and its development. This note intends to find out the relevance of the project proposal from an urban development perspective and not getting deep into the environmental, social and cultural issues. The project is appraised with respect to the context in which it was planned more than a decade ago and how relevant this project is after a decade in a state which is still having lot of issues with respect to the roads, congestion, travel time etc.